Effects of Polystyrene Solvent Difference on Morphology of Polystyrene Layers and Viscoelastic Properties of QCM Biosensors - Susi Rahayu; Masruroh Masruroh; Djoko H Santjojo; Eka Rahmawati; Lalu A. Didik; Fadli Robiandi; Setyawan P Sakti (Natural B, Journal of Health and Environmental Sciences, 2014)
In this research, a modified QCM surface was done to improve the performance of QCM biosensors. This modification is done by coating polystyrene (Ps) on a QCM with toluena and chloroform solvents. The polystyrene coating was performed using spin coating technique, the measurement of surface roughness values using non-contact topography measurement system TMS 1200, and the viscoelastic properties was analyzed by using an electrical impedance. The analysis result using TMS 1200 shows morphologies of polystyrene produced with chloroform solvent have groovier and more porous compared to the toluena solvent. The roughness values of Ps surface with choroform and toluena is about 616.52 nm and 578.9 nm, respectively. The different surface roughness both of the solvent is caused by vapor pressure of each solvent. The vapor pressure value of chlorofrom solvent is 0.26 atm and toluena solvent of 0.037 atm. Moreover, using Sauerbrey equation is found mass of deposited ps produced with chloroform solvent is more than the toluena solvent. The mass of the polystyrene deposited on the surface of QCM with chloroform resulted about 2.23 × 10-5 ± 7.59 × 10-7 g and with toluena of 1.16 × 10-5 ±9.23 × 10-8 g. Furthermore, viscoelastic test show both polystirene layer are still rigid and have approximately 12.23 Ω impedance value. Therefore, the different solvents affect the surface morphologies of Ps.